1997
DOI: 10.1007/s002619900214
|View full text |Cite
|
Sign up to set email alerts
|

Crescent-shaped necrosis: a new imaging sign suggestive of stromal tumor of the small bowel

Abstract: We report three cases of unsuspected stromal tumors of the small bowel (STSB). These cases were diagnosed preoperatively by sonography, the imaging was completed for some with barium studies, computed tomography, magnetic resonance imaging, or angiography. To our knowledge, the use of this noninvasive technique for detecting this type of tumor has not been described in the literature. Moreover, we believe that some sonographic findings such as crescentic tumoral necrosis may appear highly suggestive of STSB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
3
1
1
Order By: Relevance
“…Rectal tumors, on the other hand, tended to show homogeneous contrast enhancement. Crescent-shaped necrosis, the Torricelli-Bernouilli sign, has been reported as a sign of large GISTs [22,23]. We only saw this sign in one case (5.2%).…”
Section: Discussioncontrasting
confidence: 47%
“…Rectal tumors, on the other hand, tended to show homogeneous contrast enhancement. Crescent-shaped necrosis, the Torricelli-Bernouilli sign, has been reported as a sign of large GISTs [22,23]. We only saw this sign in one case (5.2%).…”
Section: Discussioncontrasting
confidence: 47%
“…The HFUS technique has already been used to determine the malignancy of carcinomas. [15][16][17][18][19][20] The necrosis detected with ultrasound is seldom used as a prognostic predictor for treatment efficacy. As an example, in 1997 Kenji et al showed that it could be a relevant tool for determining the efficacy of molecules, such as Lipiocis (CIS Bio-International, Gif-sur-Yvette, France) in the treatment of hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The pelvic mass was associated with rectal and bladder infiltration. [4]. Those tumors located in the pelvis often resemble ovarian neoplasms and peritoneal carcinomatosis [1].…”
Section: Discussionmentioning
confidence: 99%